Delayed diagnosis of juvenile myoclonic epilepsy. Issue 6 (June 1992) - Grünewald, R A; Chroni, E; Panayiotopoulos, C P
Abstract : Fifteen cases of juvenile myoclonic epilepsy (JME) were identified from one hundred and eighty consecutive patients referred to a new epilepsy clinic at St Thomas' Hospital between April 1989 and December 1990, a prevalence of 8.3%. Of these, only one was referred with a putative diagnosis of JME. Diagnosis of the other patients on referral included "epilepsy", "grand mal", "temporal lobe epilepsy", "photoconvulsive epilepsy" and "alcohol-induced epilepsy". At least 11 of the 15 patients had been seen by a neurologist in the United Kingdom before referral. Definitive diagnosis was delayed by a mean of 14.5 years. In seven patients inappropriate anticonvulsants had been prescribed. Control of seizures was improved in most patients after diagnosis. Factors responsible for the delay in diagnosis include lack of familiarity with the syndrome, failure to elicit a history of myoclonic jerking and high prevalence of focal abnormalities on the EEG. Precipitation of fits by alcohol and sleep deprivation may not be recognised by the physician as part of the syndrome of JME. Diagnosis may also be delayed in patients whose absence and generalised tonic-clonic seizures pre-date myoclonic jerks.